PENGARUH PROGRAM CSR “KUTA BEACH SEA TURTLE CONSERVATION” TERHADAP BRAND IMAGE PERUSAHAAN - Ratih Kurnia Hidayati; Hendra Wijayanto (Expose: Jurnal Ilmu Komunikasi, 2018)
Abstract. This study aims to analyze the influence of corporate social responsibility (CSR), on the brand image of PT Coca Cola Amatil Indonesia Tbk. This type of research is quantitative research. The population in this study is the community around the conservation of turtles who know and follow the CSR program conducted by PT Coca Cola Amatil Indonesia Tbk. Sampling based on non-probability sampling method with purposive sampling technique with the number of 99 respondents. Data analysis used is simple regression and hypothesis test by using F test and t test. The results of this study indicate that the Corporate Social Responsibility (CSR) program has a significant impact 41,6% on the brand image of PT Coca Cola Amatil Indonesia Tbk.Keywords: Corporate Social Responsibility, Brand Image, Kuta Beach Sea Turtle Conservation